ANALISIS PENGARUH MEDIA SOSIAL TERHADAP LOYALITAS KONSUMEN DI SAYUR ORGANIK MERBABU - Bayu Murya; Lasmono Tri Sunaryanto; Hendrik Johannes Nadada (AGRIBUSINESS JOURNAL, 2019)
Merbabu Organic Vegetable is company engaged in agribusiness that sells quality fresh vegetable products produced from its own garden. Vegetable products are now starting to be marketing strategies, Merbabu Organic Vegetables need to understand what consumers really want and what things effect consumer satisfaction when making vegetable purchases. This study aims to analyze the influence of social media and quality of service to the satisfaction of vegetable consumers in Merbabu Organic Vegetables.This type of research is quantitative descripyive survey method, The sampling technique uses The Non Probability Sampling method with the number of samples used as many as 108 respondents. The data analysis technique used in SEM ( Structural Equation Modeling ) analysis, which is operated through the IBM AMOS V.22 program. Results research shows that service quality has a positive and significant effect on sonsumer satisfaction of vegetables in Organic Merbabu Vagetables.Significant indicators shape service quality factors including trust, responsiveness, assurance, empathy and physical evidence. Although social media factors show insignificant results and are negatively related, all the indicators that form such as facebook, instagram and whatsApp have significant results on social media.